2020
DOI: 10.1155/2020/9097352
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and Radiobiological Comparison of Five Techniques for Postmastectomy Radiotherapy with Simultaneous Integrated Boost

Abstract: Purpose. To compare five techniques for the postmastectomy radiotherapy (PMRT) with simultaneous integrated boost (SIB). Materials and Methods. Twenty patients with left-sided breast cancer were retrospectively selected. Five treatment plans were created for each patient: TomoDirect (TD), unblocked helical TomoTherapy (unb-HT), blocked HT (b-HT), hybrid intensity-modulated radiotherapy (hy-IMRT), and fixed-field IMRT (ff-IMRT). A dose of 50.4 Gy in 28 fractions to PTVtotal and 60.2 Gy in 28 fractions to PTVboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…4,5 On the other hand, HT increases low-dose area and mean dose of OARs, high normal tissue complication probability for the lungs and heart, and high secondary cancer complication probability for the lungs and contralateral breast. 6 HT used without block structure has a potentially higher risk of radiation pneumonitis, cardiac disease and secondary cancer. 6 On the other hand, HT with a block structure increases the number of monitor units and treatment time (TT).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 On the other hand, HT increases low-dose area and mean dose of OARs, high normal tissue complication probability for the lungs and heart, and high secondary cancer complication probability for the lungs and contralateral breast. 6 HT used without block structure has a potentially higher risk of radiation pneumonitis, cardiac disease and secondary cancer. 6 On the other hand, HT with a block structure increases the number of monitor units and treatment time (TT).…”
Section: Introductionmentioning
confidence: 99%
“…6 HT used without block structure has a potentially higher risk of radiation pneumonitis, cardiac disease and secondary cancer. 6 On the other hand, HT with a block structure increases the number of monitor units and treatment time (TT). [6][7][8] The trade-off between the TT and the plan quality should be balanced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although skin ash cannot be used in helical TomoTherapy, in which rotational beam delivery is employed, it can be used for TomoDirect, in which beam delivery occurs at a xed gantry angle. TomoDirect is advantageous for breast radiation therapy because the low-dose spread to the lungs is reduced [21,22]. Kang et al reported that skin ash maintains coverage of the target in TomoDirect plans when a setup error occurs [23].…”
Section: Introductionmentioning
confidence: 99%